North Atlantic summer storm tracks over Europe dominated by internal variability over the past millennium - Gagen, M.H.; Zorita, E.; McCarroll, D.; zahn, M.; Young, G.H.F.; Robertson, I. (Nature Geoscience, 2016)
Certain large, sustained anomalies in European temperatures in the past millennium are probably the result of internal variation. Such internal variations can modulate regional temperatures away from the expected response to greenhouse gas forcing. Here we assess the causes of European summer temperature variability over the past millennium using temperature observations, simulations and reconstructions. We find multidecadal-mean summer temperatures have varied within a span of 1 K, largely controlled by external forcing. By contrast, we find subcontinental variations, described by the temperature contrast between northern and southern Europe (the meridional temperature gradient), vary with a span of 2 K, and are controlled by internal processes. These variations are the result of redistributions of precipitation and cloud cover linked to oscillations in the position of the summer storm track. In contrast to recent twentieth-century winter-time trends, variations of the summer storm track over the past millennium show a weak response to external forcing, and instead are dominated by stochastic internal variability. We argue that the response of European summer temperatures to anthropogenic greenhouse forcing is likely to be spatially modulated by the same stochastic internal processes that have caused periods of cool, wet summers in northern Europe over the last millennium.